Overview of brics countries’ initiatives on best corporate governance practices - Charão, Felipe Pereira; de Oliveira, Oderlene Vieira (Seven Editora, 2023)
With the emergence of corporate scandals, countries were forced to implement a set of control measures. It was in this context that the best corporate governance practices emerged. Therefore, this research sought to present an overview of the initiatives of the BRICS countries regarding the best corporate governance practices. To this end, a qualitative methodology was used, made possible by documentary research. In sum, among the five countries analyzed, it can be observed that in India, South Africa, and Brazil the initiatives of best practices in public corporate governance are more developed and include a greater diversity of topics that aim to create value for society and that are achieved sustainably. It was also analyzed that in China and Russia, these initiatives are still under development and very focused on fighting corruption. DOI: https://doi.org/10.56238/devopinterscie-028